2011
DOI: 10.1248/cpb.59.1
|View full text |Cite
|
Sign up to set email alerts
|

Development of Atom-Economical Catalytic Asymmetric Reactions under Proton Transfer Conditions: Construction of Tetrasubstituted Stereogenic Centers and Their Application to Therapeutics

Abstract: The development of atom-economical catalytic asymmetric reactions based on two distinct sets of catalyst, a rare earth metal/amide-based ligand catalyst and a soft Lewis acid/hard Brønsted base catalyst, is reviewed. These catalytic systems exhibit high catalytic activity and stereoselectivity by harnessing a cooperative catalysis through hydrogen bond/metal coordination and soft-soft interactions/hard-hard interactions, respectively. The effectiveness of these cooperative catalysts is clearly delineated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 175 publications
0
3
0
Order By: Relevance
“…15,16 The efficiency with which the atoms in the starting components of a reaction are incorporated into the intended product is referred to as the AE 17 (i.e., how efficiently a reaction makes use of the reactant atoms). [18][19][20] However, because we employed two different reaction conditions to achieve identical target compounds, the AE values for the mechanochemical and traditional techniques were the same. The theoretical maximum efficiency of reactant usage is given by AE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 The efficiency with which the atoms in the starting components of a reaction are incorporated into the intended product is referred to as the AE 17 (i.e., how efficiently a reaction makes use of the reactant atoms). [18][19][20] However, because we employed two different reaction conditions to achieve identical target compounds, the AE values for the mechanochemical and traditional techniques were the same. The theoretical maximum efficiency of reactant usage is given by AE.…”
Section: Resultsmentioning
confidence: 99%
“…, how efficiently a reaction makes use of the reactant atoms). 18–20 However, because we employed two different reaction conditions to achieve identical target compounds, the AE values for the mechanochemical and traditional techniques were the same. The theoretical maximum efficiency of reactant usage is given by AE.…”
Section: Resultsmentioning
confidence: 99%
“…Multimetallic RE complexes can also function in heterogeneous catalysis. An amide-based ligand 8 , , bearing two phenol functionalities on both sides of l -Leu by amide linkage, forms an insoluble heterobimetallic complex with NdO 1/5 (O i Pr) 13/5 and NaHMDS in THF via self-assembly (Scheme ). , High-resolution ESI-MS and ICP analyses indicated that the heterogeneous catalyst comprised 8 :Nd:Na = 2:1:2, and nitroethane, which is used for catalyst preparation, is also incorporated into the catalyst.…”
Section: Multimetallic Catalystsmentioning
confidence: 99%